A comparison of VO₂max response of 15-year-old soccer athletes based on training time in the tropical climate of Bima - Firdaus Firdaus; Taty Hartati; Rabwan Satriawan; Nor Fazila Abd Malek; Shutan Arie Shandi (Physical Education and Sports: Studies and Research, 2026)
Background: VO₂max is the primary indicator of a soccer athlete's aerobic capacity, but in tropical climates like Bima, high temperatures and humidity can affect VO₂max achievement. Hence, the timing of training is an important factor to consider. Objectives: This study aims to analyze differences in VO₂max across training times (morning and afternoon) in 15-year-old youth soccer athletes from the Bima Football Association (PERSSEBI). Methods: The study used a quantitative, comparative, cross-sectional observational design. The study subjects were 45 athletes (age 15.31±0.46; height 163.12±4.35 cm; weight 55.28±3.67 kg; and body mass index (BMI) 20.78±1.18 kg/m²) from the Bima Football Association (PERSEBI), selected by purposive sampling, and divided into morning (n=23) and afternoon (n=22) training groups. VO₂max was measured using a multistage fitness test (Bleep Test). Data analysis included descriptive statistics, the Shapiro–Wilk normality test, the Levene homogeneity test, and the independent-samples t-test at a significance level of 0.05, using IBM SPSS 25. Results: The descriptive analysis showed that the average VO₂max of the morning group was 43.78 ± 2.34 ml/kg/minute, higher than that of the afternoon group (42.91 ± 2.29 ml/kg/minute). The results of the independent sample t-test showed that there was a significant difference in VO₂max between the two groups with a t value = 2.14 with df = 43 and a significant p value = 0.04 (p < 0.05) with an average difference of 0.87 ml/kg/minute indicating that the morning exercise group had a higher Vo2max value than the afternoon exercise group. Conclusions: These findings suggest that training time contributes to differences in athletes' VO₂max values in tropical environments, with morning training resulting in higher performance than afternoon training. Therefore, scheduling training that accounts for environmental conditions is crucial for optimizing athletes' VO₂max.